PENINGKATAN KEKUATAN OTOT LENGAN DAN BAHU MENGGUNAKAN LATIHAN PULL DOWN PADA ATLET TINJU PUTRI CLUB HISTOM BOXING CAMP RUMBAI - sinaga, Martin luhut; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem in this research “is there any improvement by using pull down exercise forward arms muscle power and shoulder for woman boxing athlete club histom boxing at camp rumbai?”. This research was experiment design that purpose to know the improvement of pull down exercise forwards arms muscle powers and shoulder for woman boxing athlete club histom boxing at camp rumbai. The population was 6 people, all of the woman boxing athlete club histom at rumbai. This research used total sampling design, where the total of population to be sample. The technique of taking data was from pre-test and post-test. The instrument of this research was used exspanding dynamometer to measure arms muscle power and shoulder. As a free variable was pull down exercise (X) mean while bound variable was power (Y). research data obtained and collected from early test was exspanding dynamometer. The method af tabulation the data used calculation of statistical and to measure the hypotheses used hypotheses test that proposed in this research was found the influence of pull down exercise to arms muscle power and shoulder for woman boxing athlete club histom boxing at camp rumbai. The result hypotheses test was produced tcount amount of 5,549 and ttable 2,02 on the taraf significant 0,05. It is mean that tcount>ttable. The conclusion was h1 accepted, and the significant influence from pull down exercise forward arms muscle power and shoulder for woman boxing athlete club histom boxing at camp rumbai.Keyword: Pull Down. Power, Boxing